2013
DOI: 10.14797/mdcj-9-3-174
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Cardiac Computed Tomography for Assessment of Prosthetic Aortic Valve Dysfunction with Pannus Formation

Abstract: A 61-year-old female with a history of atrial fibrillation, and a distant-history mechanical St. Jude's aortic valve replacement, presented after undergoing an episode of ventricular tachycardia and worsening heart failure. A transthoracic echocardiogram revealed a dilated left ventricle (LV) with moderately depressed ejection fraction (LVEF of 44%). The international normalized ratio (INR) was 2.1. The prosthetic valve could not be well visualized; however, the Doppler velocities were suggestive of prosthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…Using beta-blockers to reduce the heart rate before performing a CT scan makes it possible to overcome the problem of temporal resolution. Post-processing methods of cardiac CT provides complementary information for assessing the dysfunction of prosthetic valves ( 13 14 15 16 20 21 26 ), and CT-derived pannus parameters are known to correlate with the hemodynamic parameters measured on echocardiographies ( 7 8 10 12 ). However, the previous studies did not evaluate the interval changes of pannus extent in the same patients, and they could not clearly demonstrate whether the pannus formation developed suddenly, or would be enlarged over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using beta-blockers to reduce the heart rate before performing a CT scan makes it possible to overcome the problem of temporal resolution. Post-processing methods of cardiac CT provides complementary information for assessing the dysfunction of prosthetic valves ( 13 14 15 16 20 21 26 ), and CT-derived pannus parameters are known to correlate with the hemodynamic parameters measured on echocardiographies ( 7 8 10 12 ). However, the previous studies did not evaluate the interval changes of pannus extent in the same patients, and they could not clearly demonstrate whether the pannus formation developed suddenly, or would be enlarged over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, as it is often difficult to visualize the exact cause of prosthetic valve dysfunction even by TEE, cardiac CT can be used as a complementary method to more clearly evaluate the dysfunction of the prosthetic aortic valve (2,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Over the past 5 years, a few case reports [16][17][18][19] and research studies [20][21][22][23][24][25][26][27][28] with limited number of patients have been published regarding the use of multidetector computed tomography (MDCT) for the 2…”
Section: See Editorial By Bonnichsen and Pellikka See Clinical Perspementioning
confidence: 99%
“…Recently, cardiac computed tomography (CT) has become an emerging technique in the evaluation of the prosthetic valve, including evaluation of pannus. A few studies have reported the utility of cardiac CT for detection of pannus formation, a cause of prosthetic valve dysfunction or obstruction in the aortic position [4][5][6][7][8][9]. However, those studies investigated only a small number of mechanical aortic valve types.…”
Section: Introductionmentioning
confidence: 99%